2014
DOI: 10.1186/bf03351785
|View full text |Cite
|
Sign up to set email alerts
|

Effect of complex fault geometry and slip style on near-fault strong motions and static displacement

Abstract: Although there are many studies that deal with complex slip distribution or rupture propagation on an earthquake fault, they usually regard a fault system as a fault of simple geometry. Actual fault systems have highly heterogeneous slip distribution and very complicated shapes, as is often observed through field surveys of surface breaks. In this study, we synthesize seismograms including static displacement near a fault using the discrete wavenumber method in order to estimate the effects of the above types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…The combination of effects from physical heterogeneities with nonlinear dynamics of rupture results in mix of characteristic and noncharacteristic modes of slip distributions noted in both theoretical studies Rice, 1995, 1997;Zheng and Rice, 1998;Nielsen and Carlson, 2000;Perfettini et al, 2001;Shaw, 2004) and observational studies specific to subduction zone earthquakes (Thatcher, 1990;Mendoza, 1993;Boyd et al, 1995;Schwartz, 1999;Mazzotti et al, 2000;Hirata et al, 2004;Satake et al, 2006a). Recent studies have also indicated that spatial heterogeneity at scales smaller than typically resolved in seismic and geodetic inversions (Յ1 km) (cf., Perfettini et al, 2001) can have a significant effect on near-field static displacement (Honda and Yomogida, 2003;Fu and Sun, 2004). Small-scale spatial heterogeneity in slip translates to variations in local tsunami runup, though the effects are diminished with increasing propagation distance and source depth (Titov et al, 2001;Geist, 2002).…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…The combination of effects from physical heterogeneities with nonlinear dynamics of rupture results in mix of characteristic and noncharacteristic modes of slip distributions noted in both theoretical studies Rice, 1995, 1997;Zheng and Rice, 1998;Nielsen and Carlson, 2000;Perfettini et al, 2001;Shaw, 2004) and observational studies specific to subduction zone earthquakes (Thatcher, 1990;Mendoza, 1993;Boyd et al, 1995;Schwartz, 1999;Mazzotti et al, 2000;Hirata et al, 2004;Satake et al, 2006a). Recent studies have also indicated that spatial heterogeneity at scales smaller than typically resolved in seismic and geodetic inversions (Յ1 km) (cf., Perfettini et al, 2001) can have a significant effect on near-field static displacement (Honda and Yomogida, 2003;Fu and Sun, 2004). Small-scale spatial heterogeneity in slip translates to variations in local tsunami runup, though the effects are diminished with increasing propagation distance and source depth (Titov et al, 2001;Geist, 2002).…”
Section: Methodsmentioning
confidence: 96%
“…Tsunami generation models used for tsunami assessments such as presented here have been modified from models previously used for strong ground motion studies (Herrero and Bernard, 1994;Berge et al, 1998;Somerville et al, 1999;Hisada, 2000Hisada, , 2001Honda and Yomogida, 2003). At low wavenumbers, stochastic slip distributions are scaled relative to average slip or static stress drop.…”
Section: Methodsmentioning
confidence: 99%